PENGETAHUAN DAN SIKAP PETUGAS POSYANDU TENTANG PENGGUNAAN APD DI DESA PANCAWATI, KECAMATAN, KABUPATEN KARAWANG - Wendi Darmawan; Chaerani Tri Yuliana; Jumaedi, Jumaedi; Muhidin, Muhidin; Wieke Widhiantika (Journal of Innovation Research and Knowledge, 2023)
This study aims to evaluate the knowledge, attitudes, and compliance of Posyandu health workers regarding the use of personal protective equipment (PPE) in Pancawati Village, Klari District, Karawang Regency. The use of PPE by Posyandu health workers is crucial in preventing the transmission of infectious diseases, especially during the COVID-19 pandemic. The research method employed is a quantitative approach with a descriptive cross-sectional design, where all Posyandu health workers in the village (total sampling) were respondents. The results show that 45% of the health workers have good knowledge of PPE, 35% have sufficient knowledge, and 20% have poor knowledge. A positive attitude towards the use of PPE is exhibited by 50% of the workers, 30% are neutral, and 20% have a negative attitude. The compliance level in using PPE indicates that 60% are compliant, 25% are less compliant, and 15% are non-compliant. This study suggests a need for improved knowledge and attitude change among Posyandu health workers, as well as the provision of adequate and comfortable PPE to enhance compliance. The recommendations include ongoing training, attitude change campaigns, and regular monitoring to ensure better implementation of PPE use